Pengaruh Pemberdayaan, Self Efficacy, Pengembangan Karier Terhadap Kepuasan Kerja Karyawan - Srinadi, Ni Made Eka; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen, 2014)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:Cambria; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-fareast-font-family:Cambria; mso-bidi-font-family:"Times New Roman";} span.hps {mso-style-name:hps; mso-style-unhide:no;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:Calibri; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri;} @page WordSection1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> Companies must understand what causes job satisfaction and job dissatisfaction of employees , because employees who are satisfied with their jobs will work more productive and loyal to the organization , while employees who are not satisfied with their job tend to be less productive and have a desire to quit from the organization , for the organizations need to pay attention to the factors that influence job satisfaction . This study aims to determine the effect of empowerment , self-efficacy and career development to job satisfaction . The study was conducted in Cooperative Market Srinadi Klungkung with multiple linear regression analysis techniques . The sample used by 76 of the 318 respondents to the population sampling method proportional random sampling . Based on the results of the analysis found that empowerment , self-efficacy and career development of partial positive and significant effect on job satisfaction . Keywords : empowerment, self-efficacy, career development, job satisfaction
Keywords: Keywords: empowerment, self-efficacy, career development, job satisfaction